A Case Study on Measures for Growth of Precast Concrete Construction Industry in India - Murali Krishna Reddy. Raya, Sai; Kavya, k.; M. Ravindhra Krishna, Dr.; M. Janardhana, Dr. (International Journal of Engineering and Technology, 2018)
INDIA is facing a huge housing demand of more than 60 million housing units. The cast in-situ construction technology cannot meet this huge demand at the fast pace required. Some of the developed countries have successfully met similar housing demands by adopting the Precast/Prefabricated Concrete (PPC) construction technology. The PPC technology can offer faster construction with better quality and be a feasible solution to meet the huge housing demand in India. However, many Indian contractors perceive that PPC construction is costlier and less suitable than cast in-situ construction and hence, do not adopt PPC construction methods.Â Â Â